Adjective attribution - Rießler, Michael (Studies in Diversity Linguistics, 2016)
"This book is the first typological study of adjective attribution marking. Its focus lies on Northern Eurasia, although it covers many more languages and presents an ontology of morphosyntactic categories relevant to noun phrase structure in general. Beside treating synchronic data, the study contributes to historical linguistics by reconstructing the origin of new types specifically in the language contact area between the Indo-European and Uralic families."